2015
DOI: 10.1007/s40725-015-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Wood–Plastic Composite Technology

Abstract: Wood-plastic composites (WPCs) are a form of composite combining wood-based elements with polymers. The processes for manufacturing WPCs include extrusion, injection molding, and compression molding or thermoforming (pressing). Newer manufacturing processes for WPCs include additive manufacturing via fused layer modeling and laser sintering. An important constraint for polymers used in WPCs is requiring process conditions (melt temperature, pressure) that will not thermally degrade the wood filler. Wood degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 79 publications
3
109
0
3
Order By: Relevance
“…In a different report by Stark and Gardner (2008), increasing the wood particles size increased the equilibrium moisture content of the composites. Nevertheless, it was specified that the materials with larger aspect ratio are the best candidate for composite's reinforcement (Gardner, Han, & Wang, 2015). In accordance to Stark and Rowlands (2003), it was confirmed that increase in mechanical properties was found to correspond with increase in aspect ratio of particles.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In a different report by Stark and Gardner (2008), increasing the wood particles size increased the equilibrium moisture content of the composites. Nevertheless, it was specified that the materials with larger aspect ratio are the best candidate for composite's reinforcement (Gardner, Han, & Wang, 2015). In accordance to Stark and Rowlands (2003), it was confirmed that increase in mechanical properties was found to correspond with increase in aspect ratio of particles.…”
Section: Introductionsupporting
confidence: 56%
“…About 99% of particles from B. vulgaris/75-µm group had an aspect ratio of less than 4.2. According to Gardner et al (2015), the large-sized particles with high aspect ratio provided better mechanical properties than the small-sized particles. Transfer efficiency of load from matrix to wood fiber could be possibly increased with increasing fiber length/diameter ratio (Migneault, Koubaa, Erchiqui, Chaala, Englund, Krause, & Wolcott, 2008).…”
Section: Particles Size Distributionmentioning
confidence: 99%
“…De otro lado, los aditivos que hacen parte del compuesto como lubricantes, ceras con el tiempo migran hacia la superficie ayudando a incrementar la complejidad del mecanismo de adhesión (Gardner et al, 2015). En esta investigación se elaboraran juntas adhesivas a partir de substratos tipo WPC elaborados con polietileno de baja densidad y 32% en peso de harina de madera del arbusto Telinne monspessulana.…”
Section: Fig 2: Resultados De La Prueba 180º T-peel Adhesiónunclassified
“…Estos materiales ofrecen ventajas sobre los compuestos tradicionales (polímero/carga mineral), tales como alta resistencia y módulo, baja densidad, menor desgaste abrasivo en la maquinaria de proceso (Gardner et al, 2015;Gupta et al, 2007;Kim y Pal, 2010;Oporto et al, 2007). Con respecto a la madera, WPC tienen mejor estabilidad dimensional en condiciones de humedad, mayor resistencia térmica y al ataque microbiano.…”
Section: Introductionunclassified
“…In addition to increasing fuel prices, there is much pressure from environmental groups and government agencies to find other means of creating composites with more environmentally friendly processing methods and materials [1,2]. Today, rapid technological change and increased competition in many industries necessitate lighter and stronger materials for use in high-performance products [3,4]. Composite structures that can provide the desired properties are created when polymers that do not meet some of the necessary physical and/or chemical characteristics in the application fields are supported by fibers of various types and proportions [5,6].…”
Section: Introductionmentioning
confidence: 99%